Ehlers-Danlos Syndrome in the Field of Psychiatry: A Review - Ishiguro, Hiroki; Yagasaki, Hideaki; Horiuchi, Yasue (Frontiers in Psychiatry, 2022)
Ehlers-Danlos syndrome (EDS) comprises a series of rare hereditary connective tissue diseases characterized by joint hypermobility, joint dislocation, and hyperextensibility of the skin, as well as cardiovascular involvement. EDS is often associated with chronic widespread physical pain, which can lead to psychological pain. Poor awareness and limited diagnosis of EDS and related symptoms result in decreased self-esteem and confusion regarding physical sensation. Furthermore, EDS imposes substantial psychological burden on patients due to exercise restriction, scars, keloids, and subcutaneous fat accumulation on the extremities, which leads to parental overprotection and bullying experiences from other children at school age. Recent large-scale studies have suggested that patients with EDS have a higher risk of mood disorders than the general population. Other cohort studies indicated high prevalence of anorexia nervosa, addiction, obsessive compulsive disorder, and anxiety disorder were found in patients with EDS. Case reports instead indicated that some psychiatric disorders were secondary symptoms due to physical problems from EDS. Therefore, psychiatrists must be more knowledgeable and proactive about EDS in their practice. We review the previous case reports and literature for patients with EDS, along with our own case of complicated psychiatric problems, which are strongly related to early stressful situations through childhood and adolescence. This is to aid general psychiatrists in the discussion of appropriate medical management in such infrequent, yet challenging conditions.